Shell Constraints on Evolutionary Body Size–Limb Size Allometry Can Explain Morphological Conservatism in the Turtle Body Plan - Guilherme Hermanson; Serjoscha W. Evers (Ecology and Evolution)
ABSTRACT Turtles are a small clade of vertebrates despite having existed since the Late Triassic. Turtles have a conservative body plan relative to other amniotes, characterized by the presence of a shell and quadrupedality. This morphology is even retained in strong ecological specialists, such as sea turtles, which are secondarily adapted to marine locomotion by strong allometric scaling in their hands. It is possible that the body plan of turtles is strongly influenced by the presence of the shell, acting as a constraint to achieving greater diversity of body forms. Here, we explore the evolutionary allometric relationships of fore‐ and hindlimb stylopodia (i.e., humerus and femur) with one another as well as their relationship with shell size (carapace length) to assess evidence of constraint. All turtles, including Triassic shelled stem turtles, have near‐isometric relationships that do not vary strongly between clades, and evolve at slow evolutionary rates. This indeed indicates that body proportions of turtles are constrained to a narrow range of possibilities. Minor allometric deviations are seen in highly aquatic sea turtles and softshell turtles, which modified their shells by bone losses. Our allometric regressions allow accurate body size estimations for fossils. Several independent sea turtle lineages converged on maximum sizes of 2.2 m of shell length, which may be a biological maximum for the group.